Mil Ribeiras: uma cartografia das heterotopias, disciplinamentos e rasuras na produção do espaço urbano - Cunha, Carlos Henrique Pessoa (2020)
This research, in all its maps, pursued the dynamics of the production of heterotopic states in a urban space – Ribeira neighborgood, Natal/RN – in order to understand which power flows acted, always in connection, in a type of composition that coincides precisely with the very making of espace. Ribeira, like any other, is a not a neighborhood that has remained unchanged over time, that is, it can be said that neither of its beginning nor of its end, but only in the dynamics of its constant production. How many Ribeiras have existed and still exist in the same geophysical framework, sometimes simultaneously, and what are the flows of power that have come together over time (twentieth and twentyfist century), driving collective assemblages that engineered all these Ribeiras? Because it is one of the oldest areas of Natal, and because part of what was officially determined as the city’s historic center, Ribeira was well suited to the thesis proposal, as it allowed to map how molar and molecular flows were composed in time, producing existential territorialities, movements of intersection (not in a sense of opposition, but of connection) between the various lines of segmentarities presente in the construtuction of Ribeira, that is, how the hard and molar lines acted to normalize, discipline and create faces for space and to the lives that might or might not take places there, while pulses of less tame and dissident lives moved to tear off masks, wreck faces, and aim for the creation of new worlds. Thus, we seek to tense urban narratives with a focus solely on disciplining urban projects, such as the Overcoding Retrotopic Capture programs of historic centers. We think of other possibilities for experiencing, communicating and consuming the urban spaces, by interviewing and giving rise to urban and marginalized texts that do not negate the normative forces, but bring new elements to the realities. This academic experience was viscerally connected with the open philosophy of multiplicity proposed by Deleuze and Guattari, which pointed to new theoretical, epistemological and methodological paths.